The social media marketing book - Zarrella, Dan. (Beijing ; Sebastopol, CA : O'Reilly, 2010)
Describes various social networking sites, blogs, and forums and offers strategies on effective marketing tactics.
Blogging -- Twitter and microblogging -- Social networking -- Media sharing -- Social news and bookmarking -- Ratings and reviews -- Forums -- Virtual worlds -- Strategy, tactics, and practice -- Measurement.
Includes index.
Keywords: Social media; Business enterprises -- Computer network resources; Internet marketing